Spatiotemporal Assessment and Modelling of Roof-Harvested Rainwater Quality in Kigezi Highlands, Uganda - Philip, Tibenderana; Moses, Nduhira Twesigye-omwe; Agwe, Tobby Michael; Abdulkadir, Taofeeq S; Denis, Byamukama (Kabale University, 2023)
Water is an everlasting free resource that is vital for life (Rahman, et al., 2014). Access to water supply is essential to good life and health. It is crucial and pivotal to many other goals highlighted in the United Nation’s Sustainable Development Goals (SDGs). Sustainable access to water for potable and non-potable uses continues to pose enormous challenges. The challenge of achieving water security in Africa is contingent upon the hydrological variability and its extremes (UN-Water, 2010). However, the availability of freshwater resources has become a major challenge facing humanity worldwide especially in developing countries. This situation has further been aggravated by a high rate of urbanization, population growth, rising water demand, continuous depletion of fresh surface water and groundwater, climate change, water governance, extreme social inequality and pollution (Struk-Sokolowska, et al., 2020, Balogun et al., 2016). These situations require that water resources be satisfactorily managed in terms of quantity and quality to meet the current demands and attain future sustainability.